The Impact of Servant Leadership on Employee Performance - Ari, Reza Yayang; Agustyawati, Dwi; Perdana, Deki (International Journal of Management Progress, 2024)
Leadership is a crucial factor in achieving organizational success. To accomplish organizational goals, effective leadership skills are essential because leaders have the ability to influence, motivate, and direct individuals within the organization to work collaboratively toward common objectives. Therefore, a leader can be regarded as the driving engine that propels the organization forward. In today’s competitive business environment, companies must adapt to various challenges, particularly those involving human resources, which serve as one of the most valuable assets of the organization. Other resources, such as machinery and capital, will not function optimally without strong employee performance. This study employed a quantitative approach using questionnaires, literature reviews, and documentation as data collection methods. The data were analyzed using simple regression analysis, including the t-test, r-test, classical assumption test, validity test, and reliability test. The findings indicate that the servant leadership variable (X) has a significant influence on employee performance (Y) at CV Bukit Memory. The correlation coefficient (r-count) of 0.484 exceeds the r-table value of 0.320 at a 5% significance level (N = 38), leading to the rejection of H₀ and acceptance of Hₐ. The coefficient of determination (23.5%) shows a positive effect, meaning that stronger implementation of servant leadership enhances employee performance, while the remaining 76.5% is influenced by other factors not examined in this study.